2023
DOI: 10.1038/s41598-022-26476-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dialysis modalities on risk of hospitalization for gastrointestinal bleeding

Abstract: Dialysis patients are at risk of both thromboembolic and bleeding events, while thromboembolism prevention and treatment may confer a risk of major bleeding. Gastrointestinal (GI) bleeding is a great concern which can result in high subsequent mortality rates. Our object was to clarify whether hemodialysis (HD) and peritoneal dialysis (PD) confer different incidence of GI bleeding, and further assist individualized decision-making on dialysis modalities. We conducted a population-based retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Gastrointestinal bleeding (GIB) is a common and often underestimated medical condition that subsequently leads to increased morbidity and mortality among patients with CKD [ 5 ]. Several studies have reported the growing problem of GIB in patients with CKD [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal bleeding (GIB) is a common and often underestimated medical condition that subsequently leads to increased morbidity and mortality among patients with CKD [ 5 ]. Several studies have reported the growing problem of GIB in patients with CKD [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%